Generation of Hydroxyl Radical by Enzymes, Chemicals, and Human Phagocytes In Vitro: DETECTION WITH THE ANTI-INFLAMMATORY AGENT, DIMETHYL SULFOXIDE - Repine, John E. (1979)
Methane (CH(4)) production from the anti-inflammatory agent, dimethyl sulfoxide (DMSO), was used to measure ·OH from chemical reactions or human phagocytes. Reactions producing ·OH (xanthine/xanthine oxidase or Fe(++)/EDTA/H(2)O(2)) generated CH(4) from DMSO, whereas reactions yielding primarily O-(2̇) or H(2)O(2) failed to produce CH(4). Neutrophils (PMN), monocytes, and alveolar macrophages also produced CH(4) from DMSO. Mass spectroscopy using d(6)-DMSO showed formation of d(3)-CH(4) indicating that CH(4) was derived from DMSO. Methane generation by normal but not chronic granulomatous disease or heat-killed phagocytes increased after stimulation with opsonized zymosan particles or the chemical, phorbol myristate acetate. Methane production from DMSO increased as the number of stimulated PMN was increased and the kinetics of CH(4) production approximated other metabolic activities of stimulated PMN. Methane production from stimulated phagocytes and DMSO was markedly decreased by purportedly potent ·OH scavengers (thiourea or tryptophane) and diminished to lesser degrees by weaker ·OH scavengers (mannitol, ethanol, or sodium benzoate). Superoxide dismutase or catalase also decreased CH(4) production but urea, albumin, inactivated superoxide dismutase, or boiled catalase had no appreciable effect. The results suggest that the production of CH(4) from DMSO may reflect release of ·OH from both chemical systems and phagocytic cells. Interaction of the nontoxic, highly permeable DMSO with ·OH may explain the anti-inflammatory actions of DMSO and provide a useful measurement of ·OH in vitro and in vivo.